Macular carotenoid supplementation in subjects with atypical spatial profiles of macular pigment - Nolan, John M.; Akkali, Mukunda C.; Loughman, James; Howard, Alan N.; Beatty, Stephen (Experimental eye research, 2012)
This study was designed to investigate the impact of macular carotenoid supplementation on the spatial profile of macular pigment (MP) in subjects where the profile does not exhibit the typical central peak (i.e. peaked MP at foveal epicentre). Thirty one healthy subjects with such atypical MP spatial profiles were assigned to one of three intervention groups: Group 1: (n = 10), 20 mg/day lutein (L), 2 mg/day zeaxanthin (Z); Group 2: (n = 10), 10 mg/day meso-zeaxanthin (MZ), 10 mg/day L, 2 mg/day Z; Group 3: (n = 10), 17 mg/day MZ, 3 mg/day L, 2 mg/day Z. Subjects were instructed to take one capsule daily over an 8-week period. MP at 0.25°, 0.5°, 1°, 1.75°and 3° was measured using customized-heterochromatic flicker photometry at baseline, four weeks and 8 weeks. Over the study period, we report no statistically significant increase in MP at any eccentricity in Group 1 (p > 0.05, for all eccentricities). There was a trend towards an increase in MP at all eccentricities in Group 2, with a significant increase found at 0.25° and 0.50° (p = 0.000 and p = 0.016, respectively). There was a statistically significant increase evident in MP at 0.25° in Group 3 (p = 0.005), but at no other eccentricity (p > 0.05, for all other). We report that the typical central peak of MP can be realised in subjects with atypical spatial profiles, following supplementation with a preparation containing all three macular carotenoids, but not with a supplement lacking MZ. The implications of our findings, in terms of visual performance and/or a (photo)-protective effect, warrant additional study. ► The meso-zeaxanthin supplement normalises the spatial profile of macular pigment. ► Meso-zeaxanthin is required to realise central MP in atypical profiles. ► All three macular carotenoids are needed for rapid augmentation of macular pigment.